Experimental determination of the scattering length for positron scattering from krypton - Zecca, A.; Chiari, L.; Trainotti, E.; Fursa, Dmitry; Bray, Igor; Brunger, M. (Springer, 2011)
We report the first experimentally supported determination of the scattering length for positron scattering from krypton. Our result of -10.3 ± 1.5 a.u. compares favourably with that from a convergent close coupling calculation performed as a part of this investigation (-9.5 a.u.), and also with an earlier many body theory calculation of -10.1 a.u. from Gribakin and Ludlow [Phys. Rev. A 70, 032720 (2004)] and a polarized-orbital result of -10.4 a.u. from McEachran et al. [J. Phys. B 13, 1281 (1980)]. The present experimental scattering length supports the existence of a low-lying positron-krypton virtual state (Surko et al. [J. Phys. B 38, R57 (2005)]) at an energy ε = 0.13 eV.